PERBANDINGAN EFEKTIFITAS ANTIHIPERTENSI DAUN TANAMAN HERBAL MENURUNKAN TEKANAN DARAH PADA TIKUS BETINA INDUKSI HIPERTENSI - Fitra Wahyuni; Renowati Renowati; Ummu Habibah; Mona Dewi Utari; Nia Desriva (Ensiklopedia of Journal, 2022)
The purpose of this study was to compare the effectiveness of leaf decoction of antihypertensive herbs commonly used in Indonesia to lower blood pressure. This study used female rats induced hypertension as animal models. In this experimental study, rats were divided into seven experimental groups consisting of four rats for each group. Rats have induced hypertension with a dose of 2.5 mg/kg BW of prednisone and 2.5% NaCl. Hypertension induction for rats was carried out for 14 days, treatment with herbs of leaf decoction (soursop, starfruit, celery, and salam) with a dose of 200 mg/kg BW for 14 days. Rat's blood pressure was measured by the tail-cuff method at 0 days, 14 days, and 28 days. Statistical analysis used was an analysis of variance with ANOVA followed by a comparison between treatments with Dunnet's test. This study showed that all the herbal plants given were able to reduce systolic and diastolic blood pressure in female rats induced by hypertension, especially boiled celery leaves and star fruit leaves with p-value < 0.05.